Analisa Ekonomi Penerapan Metode Peak Clipping Dan Stategic Conservation Pada Pola Beban Listrik Sektor Rumah Tangga Di Kota Pekanbaru - Ali, Irsan Taufik; Badri, Mutiarahma; Nurhalim, Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The use of electrical energy by the customers are still not optimum, especially in the evening at peak load periodes. One method to reduce the peak load by applying load management on the customer side (demand side management) which include are peak clipping (PC) and strategic conservation (SC). The analysis was focused on the household load i.e. lamp, television and fan in Pekanbaru. This thesis explores benefit of implementation peak clipping and strategic conservation programs in economic criteria by doing economic calculation at city scale and household appliances. Based on the calculation and analysis, by implementation of peak clipping’s and strategic conservation’s method on lamps, televisions and fans has the potential to result in economic benefits which in fifteenth year NPV becomes Rp. 188.675.730.000,-. Moreover, the implementation of strategic conservation on the each lamps and televisions also has potential result in economic benefits especially for household on fare groups R1/900-2200VA.Keywords : Peak clipping, strategic conservation, economic criteria